STUDI SISTEM PROTEKSI LINE CURRENT DIFFERENTIAL RELAY PADA SALURAN TRANSMISI 150 KV - Dharmawan, N. B.; Ariastina, W. G.; Amrita, A. A. N. (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i01.p22, 2020)
Increasing electricity demand in South Bali requires a reliable electrical system. Reliable electrical systems can be achieved in various ways, one of which is the replacement of high voltage overhead line to high voltage underground cable. The replacement high voltage overhead line to high voltage underground cable requires adjustment of the protection system. The previous main protection system used in high voltage overhead line is distance relay, while the protection system for the new transmission network is line current differential relay. The purpose of this study is to analyze GIS Pesanggaran to GI Nusa Dua transmission line’s protection system. The covered in this analysis is to power flow analysis simulation, 3 phase short circuit simulation, relays setting calculation and testing the relays setting.The power flow simulation showed that the current at peak load from GIS Pesanggaran to GI Nusa Dua is 337 A. The 3 phase short circuit simulation showed that the largest short circuit, if a fault occurs on the GI Nusa Dua of 9.54 kA. The relays setting calcullation showed that of 0,2 A with 20 % slope for Is1 and 2 A with 150% slope for Is2. The results showed that the relays setting has worked properly.